Metaforyka troski o siebie w "Żywocie człowieka poczciwego" = The metaphoricity of "the self care" in "Żywot człowieka poczciwego" ["The life of a humble man"] - Maliszewski, Bartłomiej (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The aim of the study is to analyse the metaphors and analogies which are used in "Żywot człowieka poczciwego" ["The life of a humble man"] to postulate the self care (recommendations concern?ing sagacious emulation, getting rid of finding vices). While discussing the metaphors and analogies, we pay attention to their cognitive function (the metaphor is perceived as a means of capturing abstract themes), the persuasive function (the metaphor is seen as a means of influencing the addressee) and the culture-forming function (the metaphor is viewed as a recorded exponent of the past reality and the addresser's world of values).
Keywords: Rej, Mikołaj (1505-1569); metafora; pareneza; troska o siebie; metaphor; parenesis; the care of the self